A Novel Classification of 3D Rib Cage Deformity in Subjects With Adolescent Idiopathic Scoliosis. Issue 9 (November 2021) - Assi, Ayman; Karam, Mohamad; Skalli, Wafa; Vergari, Claudio; Vialle, Raphael; Pietton, Raphael; Bizdikian, Aren J.; Kharrat, Khalil; Dubousset, Jean; Ghanem, Ismat
Abstract : Study Design: This was a multicentric cross-sectional descriptive study. Objective: To analyze patterns of 3D rib cage deformity in subjects with adolescent idiopathic scoliosis (AIS) and their relationship with the spinal deformity. Summary of Background Data: Subjects with AIS present with rib cage deformity that can affect respiratory functions. The 3D rib cage deformities in AIS and their relationship to the spinal deformity are still unelucidated. Methods: A total of 200 AIS and 71 controls underwent low-dose biplanar x-rays and had their spine and rib cage reconstructed in 3-dimensional (D). Classic spinopelvic parameters were calculated in 3D and: rib cage gibbosity, thickness, width, volume and volumetric spinal penetration index (VSPI). Subjects with AIS were classified as: group I with mild rib cage deformity (n=88), group II with severe rib cage deformity (n=112) subgrouped into IIa (high gibbosity, n=48), IIb (high VSPI, n=48), and IIc (both high gibbosity and VSPI, n=16). Results: Groups IIa and IIb had a higher Cobb angle (33 vs. 54 degrees and 46 degrees, respectively) and torsion index (11 vs. 14 degrees and 13 degrees, respectively) than group I. Group IIb showed more severe hypokyphosis (IIb=21 degrees; IIa=33 degrees; I=36 degrees; control=42 degrees) with a reduced rib cage volume (IIb=4731 cm 3 ; IIa=4985 cm 3 ; I=5257 cm 3 ; control=5254 cm 3 ) and thickness (IIb=135 mm; IIa=148 mm; I=144 mm; control=144 mm). Group IIa showed an increasingly large local gibbosity descending from proximal to distal levels and did not follow the axial rotation of the spine. Group IIc showed characteristics of both groups IIa and IIb. Conclusions: This new classification of 3D rib cage deformity in AIS shows that the management of cases with high VSPI (groups IIb and IIc) should focus on restoring as much kyphosis as possible to avoid respiratory repercussions. Treatment indications in groups I and IIa would follow the consensual basic principles reported in the literature regarding bracing and surgery.